The experience of families in face of the finiteness of their children in the process of adopting palliative care - Miriam Neis; Helena Becker Issi; Maria da Graça Corso da Motta; Cristianne Maria Famer Rocha; Paulo Roberto Antonacci Carvalho (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To reveal the experience of family members after learning their child would adopt palliative care. Method: Phenomenological research on Heidegger's perspective. The participants were eleven family members of children who were recommended palliative care in the Pediatric Intensive Care Unit from a university hospital in southern Brazil. The statements were obtained in a semi-structured interview, from January to November/2017, and submitted to Heidegger's theoretical-philosophical analysis. Research approved by the institution's Ethical Committee. Results: The communication of palliative care triggers the perception of the child's existencial facticity in the Family, revealing reactions explained in the thematic dimensions: "Coping with the finiteness of the child when confronted with the proposal of adopting palliative care" and "The need for compassionate and attentive care". Final considerations: Phenomenology allows us to understand the parent's existential purpose. An understanding perspective can help interdisciplinary teams to communicate the adoption of palliative care in a sensitive and ethical way, focusing on the best interest of the child.